INVESTIGASI EKSPERIMENTAL PERILAKU PROFIL BAJA RINGAN BERPENAMPANG PERSEGI AKIBAT INTERAKSI BEBAN TEKAN MEMUSAT DAN MOMEN LENTUR[Behaviour Experimental Investigation of A Thin-Walled Steel Square Hollow Secton Beam Affected by the Interaction of Concentrated Compressive Load and Bending Moment] - Kadir, Andi Muhdiar; Priadi, Dedi; Siradj, Eddy S; Setiyono, Harkali (Jurnal Metalurgi, 2013)
This paper is a part of research program that focused in developing a strength analytical method of a thin-walled steel square pipe (Square Hollow Section/SHS) affected by the interaction of concentrated-compressive load and bending moment that its based on plastic mechanisms and elastic theories (cut-off strength), and its accuracy will then be verified by data obtain from an experimental approach. In the first stage of this research program, the strength of SHS pipe is analyzed by using of existing code design namely British Standard (BS 5950 Part 5 1987) that is implemented according to a direct method and double channels one. In the experimental method is performing preleminary test that basic material identification and main test that strength measure of SHS under interaction of concentrated-compressive load and bending moment. The data test results of basic material is used as data input in strength analytical method of a thin-walled steel square pipe by British Standard meanwhile the test results of a thin-walled steel square pipe is use as reference of strength analysis method results. The results of SHS pipe strength show that the strength estimation using the double channels method has a close value to the experimental one (scattered in between 2% up to 7%) and this is within acceptable limits of  20 %. This first data results of experimental and strength analysis by design code are accurate enough and it will be compare with the result of developing a strength analytical method at the next step research.